Analisis Hukum terkait Restrukturisasi BUMN melalui Konsolidasi Pembentukan Bank Syariah Indonesia: Aspek Regulasi dan Pengawasan - Sela Sulaksmi Widyatamaka; Assyura Zumarnis; Nyulistiowati Suryanti; Deviana Yuanitasari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research was made to find out how the application of law in the banking consolidation system which is the embodiment of a company owned by a State-Owned Enterprises (SOEs). Consolidation is the process of merging two or more companies to form one new company where the old company that has merged will disappear as a legal effect, such as Bank Mandiri Syariah, Bank BRI Syariah, and Bank BNI Syariah forming Bank Syariah Indonesia. With the consolidation mechanism, new legal consequences arise that will become the basis for running the consolidated banking operational system. The method used in this research is normative juridical with analytical descriptive aspects as the basis for assessing legal concepts in the research. Based on the results of the research, the consolidation of Islamic banking uses the same mechanism system as a limited liability company as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies. However, Islamic banking has different aspects of supervision from conventional banking in general. In addition, Bank Syariah Indonesia Tbk as an Islamic bank has also achieved the goals of a SOEs as mandated by law.